Analyzing frequency spectrum and Total Harmonic Distortion for high switching frequency operation of GaN-based filter-less multilevel cascaded H-bridge inverter - Ramkrishna Mishan; Xingang Fu; Chanakya Hingu; Poria Fajri (e-Prime: Advances in Electrical Engineering, Electronics and Energy)
The recent innovations in the utilization of high switching frequency operation of Gallium Nitride (GaN) switches may further transform the output voltage’s frequency spectrum and Total Harmonic Distortion (THD), facilitating the possibility of operating in filter-less conditions, smaller size and cost-effectiveness, albeit with certain drawbacks. This investigation delves into the capability of GaN switches to achieve MHz switching frequencies within symmetric, higher multilevel cascaded H-bridge (CHB) configurations. The switching phase delay and cell voltage are set accurately for higher-level CHB and high switching frequency operation. Despite the advantageous electrical properties of GaN switches for switching operation, their assimilation into high multilevel CHB inverter designs at MHz frequencies poses considerable challenges regarding efficiency, control, and the minimization of THD. This study employs a simulation software PLECS model of the GaN switch to assess symmetric phase-shift pulse width modulation techniques. Later, the efficacy of filterless GaN-based multilevel inverters in diminishing THD is thoroughly investigated using the Texas Instruments microcontroller (TMS320F28335) and the GaN half-bridge EVALUATION BOARD: GS66516T from GaN System Inc. (now Infineon Technologies AG). The simulation results have demonstrated when using 25-level CHB inverters, the THD reaches the 5% requirements, which satisfies the needs of most power electronics applications. Experimental outcomes indicate a notable frequency spectrum change with high-level and high switching frequency operation, corroborating the efficacy of filterless GaN switches. This paper analyzes the Fast Fourier Transform (FFT) and THD of the CHB inverter output from the PLECS simulation model and the actual hardware inverter terminal-end voltage outputs. This comparison identifies the optimum switching frequency operation range for specific levels in the PLECS simulation and the actual CHB inverter.